Study of the Classical sites of Armenia during the years of the Third Republic (1991-2018) - Zardaryan, Mkrtich H. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The end of the 20th century in Armenia was marked by several events which had a turning influence on the political status of the country, on its state system, and on the way of life of the population. These radical changes naturally affected scientific life, including the process of archaeological research. Under new, quite difficult conditions, the number of sites studied and the scale of research was considerably limited, and the continuation of existing works disturbed. Nevertheless, under the new political and economic situation the opportunities for international research projects increased for Armenian archaeologists. This political and social-economic transformation was naturally reflected in the archaeological studies of the Classical period in Armenia too; compared with the 1980s, the last decade of the 20th century saw a reduction in the number of sites researched and the ongoing excavations scaled back. During that time span only limited works were carried out in the areas of the capitals of Armavir and Artashat (see below).